Makna Tradisi Ruwatan Adat Jawa Bagi Anak Perempuan Tunggal Sebelum Melakukan Pernikahan di Desa Pulungdowo Kecamatan Tumpang Kabupaten Malang - Dinna Eka Graha Lestari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2020)
Javanese traditional ruwatan tradition for single daughters before marriage in Pulungdowo Village, Tumpang District, Malang Regency. This research is motivated by the existence of marriage rules on single daughters. Where is the only child when going to marriage must do ruwatan first. The purpose of ruwatan is to eliminate the danger that will befall an only child and so that it does not become food from Batarakala. This ruwatan tradition is mandatory, meaning that if it does not carry out ruwatan then the only child is believed to get bad luck or distress.